Systemic analysis of urinary stones from the Northern, Eastern, Central, Southern and Southwest China by a multi-center study - Rui-hong Ma; Xiao-bing Luo; Qin Li; Hai-qiang Zhong (BMC Urology, 2018)
Abstract Background To provide some basis for the prevention of urinary stones in general population, we did a systemic analysis of urinary stones from Northern, Eastern, Central, Southern and Southwest China by a multi-center study. Methods A total of 11,157 urinary stones from Northern, Eastern, Central, Southern and Southwest China were obtained and analyzed by Fourier transform infrared spectroscopy. Combined with scanning electron microscopy and X-ray energy spectrometer, urinary stones were classified into different types. Furthermore, the correlation between stone types and clinical characteristics, as well as their regional distribution were elucidated. Results Calcium oxalate stones were the most common type in each region, followed by calcium oxalate-calcium phosphate mixed stones, uric acid stones and calcium phosphate stones. The distribution of calcium oxalate stones were highest prevalence in Southwest China (67.9%, P < 0.05), followed by Eastern and Northern China. Anhydrous uric acid stones, with a constituent ratio of 19.3% in Southern China, and 13.7% in Central China, were significantly higher than that in other regions (P < 0.05). Elements analysis indicated varieties among stone types as well as distribution regions. Moreover, the clinical characteristics were highly correlated with stone types and anatomical locations but not their distribution regions. Conclusions The material and elements composition of urinary stones among different regions showed some varieties. Calcium oxalate stone has the highest constituent ratio in Southwest China, while anhydrous uric acid stone has the highest constituent ratio in Southern China. Moreover, the clinical characteristics were highly correlated with stone types and anatomical locations but not their distribution regions.